1999
DOI: 10.2135/cropsci1999.0011183x003900010008x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Hull Percentage in Oat

Abstract: Low hull percentage has long been recognized as a valuable measure of grain quality in oat, Avena sativa L.; however, reliable selection for low hull percentage has been impeded by a lack of understanding of its heritability. The objective of this study was to investigate the heritability of hull percentage in three oat crosses, involving the cultivars Cascade, Robert, and AC Marie, which have 30, 25, and 23% hull, respectively. Populations F2‐deriveF4 through F7 lines were grow in replicated or unreplicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
0
13
0
6
Order By: Relevance
“…Thus, conditions unfavourable for grain filling result in incompletely filled grains and tend to reduce the groat to hull ratio. Ronald et al (1999) indicated that groat weight correlated only modestly with proportion of hull and reported high broad-sense heritability estimates for hull percentage, which indicates the potential for selecting for reduced hull content.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, conditions unfavourable for grain filling result in incompletely filled grains and tend to reduce the groat to hull ratio. Ronald et al (1999) indicated that groat weight correlated only modestly with proportion of hull and reported high broad-sense heritability estimates for hull percentage, which indicates the potential for selecting for reduced hull content.…”
Section: Introductionmentioning
confidence: 97%
“…Such changes are achieved by breeding for low hull content (Ronald et al 1999). The composition of the hull can also be modified by breeding, but Welch et al (1983) found that even though significant genetic differences in hull composition existed, the range was modest.…”
Section: Introductionmentioning
confidence: 99%
“…Pada penelitian ini, karakter yang memiliki koefisien keragaman tinggi (> 20%) adalah ASI, bobot kering tongkol, bobot kering biji, jumlah biji/tongkol, jumlah biji/baris, dan bobot tongkol/plot. Koefisien keragaman genetik yang besar menunjukkan bahwa manipulasi genetik yang dilakukan akan memiliki peluang yang besar, sedangkan koefisien keragaman genetik kecil akan memberi peluang keberhasilan yang sangat kecil bila sifat tersebut diperbaiki (Ronald et al 1999 yang tinggi dapat digunakan secara langsung sebagai karakter seleksi (Sudarmadji et al 2007). …”
Section: Pendugaan Komponen Ragam Dan Nilai Heritabilitasunclassified
“…Unfortunately, problems with preharvest sprouting, threshability, rancidity, a wide range of kernel sizes as well as its relatively low tolerance to limited soil water content (Nita, 2003) are its main drawbacks (Forsberg and Reeves, 1992). Moreover, the husk plays a crucial role in protecting the groat from damage (Burrows, 1986) and pathogenic attack (Ronald et al, 1999). Nevertheless, dehusked conventional oat, does not achieve comparable economic result as naked one, as dehusking costs and disposition of the husk waste is considerably large (Kirkkari, 2008).…”
Section: Plant Materials and Dna Extractionsmentioning
confidence: 99%
“…Moreover, husk decreases bulk density, reducing storage and transport efficiency (Burrows, 1986). Its percentage ranges from a minimum of 21% to a maximum of 41% (Ronald et al, 1999). Husks comprise mainly of cell wall (> 83%) with nearly equal quantities of cellulose and hemicellulose (30-35%) (Welch et al, 1983).…”
Section: Introductionmentioning
confidence: 99%